Feasibility and efficacy of spinal microtubular technique for resection of lumbar dumbbell-shaped tumors - Wang, Rui; Liang, Zeyan; Chen, Yan; Xu, Xiongjie; Chen, Chunmei (Frontiers in Oncology, 2022)
Objective: Minimally invasive surgical resection of lumbar dumbbell-shaped tumors is rarely reported. We retrospectively collected clinical data of lumbar dumbbell-shaped tumors treated with the spinal microtubular technique to evaluate the feasibility, complications and efficacy of the surgical methods. Methods: From September 2013 to August 2021, clinical data of patients with lumbar dumbbell-shaped tumors that underwent paravertebral approach and micro-tubular tumorectomy (PAMT) were collected; neurological function was assessed using the pain visual analog scale (VAS) and the Japanese Orthopaedic Association (JOA) score. Results: A total of 46 patients that underwent PAMT were included in this study. In all patients, total resection of the tumor was performed at one stage (100%). The median follow-up period was 27.5 months (P25, P75: 16.5- 57 months). Symptoms such as pain or lower extremity weakness were significantly relieved in 46 patients. The postoperative VAS score and JOA score were significantly higher compared with preoperative scores (p <0.001), and the patients had no tumor recurrence or spinal instability. According to the Eden classification, there were 7 cases of type I, 8 cases of type II, 15 cases of type III, and 16 cases of type IV. In the comparison of the improvement of VAS score at 12 months after PAMT, there were significant differences among different types of tumors (H =15.756, p =0.001); type I was better than type III (Z =2.768, p =0.029) and type IV (Z =2.763, p =0.029), and type II was also better than type III (Z =2.679, p =0.037) and type IV (Z =2.708, p =0.034). With respect to estimated blood loss (Z =-3.041, p =0.013) and postoperative hospital stays (Z =-3.003, p =0.014), type IV was less than type III; and type IV was also less than type II about operation time (Z =-2.653, p =0.040). Conclusion: In small lumbar dumbbell-shaped tumors, PAMT is indicated for Eden types I-IV and different pathological types of tumors, and can achieve complete resection of the tumor (GTR) in one stage with a good prognosis.